"Garbi" Mandarin: A New Late-maturing Triploid Hybrid - Aleza, Pablo; Cuenca, José; Juárez, José; Pina, José A.; Navarro, Luis (2017)
Citrus is the most extensively produced fruit tree crop in the world (FAO, Food and Agriculture Organization, 2009). There are two clearly differentiated markets: fresh fruit and processed juice. In 2007, the main citrus fruit-producing countries were China (17.9%), Brazil (17.8%), the Mediterranean countries (17.1%), and the United States (8.5%) (FAO, Food and Agriculture Organization, 2009). These areas account for more of two-thirds of the total production of citrus fruits. In the Mediterranean area, citrus fruits are primarily produced for the fresh fruit market. Spain is the principal producer in the area with a total planted area of 330,000 ha and a production 6.3 million tons. Seedlessness is one of the most important characteristics for mandarin on the fresh fruit market, because consumers do not accept seeded fruits. Parthenocarpy is an essential trait for seedless fruit production, and this characteristic is present in citrus germplasm. Triploidy gives rise to seedless commercial cultivars. However, triploid plants have very low fertility, are generally sterile, and do not induce seeds in other cultivars by crosspollination (Frost and Soost, 1968). Several methods have been developed to obtain triploid citrus (Navarro et al., 2002; Ollitrault et al., 2008). One exploits natural events of polyploidization such as 2n gametes using embryo rescue and flow cytometry to select triploids in 2x · 2x crosses. Second meiotic division restitution has been proposed for diploid megagametophyte development in clementine (Luro et al., 2004), whereas Chen et al. (2008) proposed first meiotic division restitution in sweet oranges. In Spain, the structure of mandarin cultivars poses several problems. Mandarins include satsumas, clementines, and mandarin hybrids. Satsumas are harvested from the beginning of September until the beginning of November. They are cultivars with a high degree of parthenocarpy and have sterile pollen and ovules. Clementines are the most representative cultivars of mandarin in Spain. They are picked from mid-September until mid-February. They are self-incompatible, but pollen and ovules are viable, being able to pollinate and to be pollinated by other cultivars. Mandarin hybrids, like ‘Nova’ [C. clementina · (C. paradisi · C. tangerina)], ‘Fortune’ (C. clementina · C. tangerina), and ‘Ortanique’ tangor (natural hybrid between mandarin and C. sinensis), were introduced in the Spanish citriculture to cover the demand of late-season mandarins by international markets. They enable the harvesting period to be extended until May. These hybrids are also self-incompatible, but pollen and ovules are viable and cross-pollinate with clementines, producing fruits with seeds in both groups of cultivars. A triploid breeding program has been carried out in Spain since 1996 based on sexual hybridization, embryo rescue, and ploidy analysis by flow cytometry (Navarro et al., 2002). The objective is to produce new high–quality, late-season and seedless triploid mandarin hybrids. In this article, we describe ‘Garbı´’ mandarin, a new triploid hybrid developed within this program characterized by its high-quality, late-season ripening and seedless fruits.